Use of Social Media for Modern Reference Service Delivery in Academic Libraries in Nigeria - F.N, Okoroma (International Journal of Asian Social Science, 2018)
The technology driven environment today is pressing hard on every aspect of human endeavour. This demands that academic libraries use the latest technologies and trends to make their services more popular, interesting and user friendly. Appropriate and adequate integration of the social media network will evolve in the recasting of reference services, as it provides an avenue to reach out to the users in their preferred environments as well as aid in a more dynamic, exciting and easier reference services delivery. There is dearth of literature on the use of social media for reference services in academic libraries, particularly in Nigeria which can be attributed to scarcity of research on this topical area. This work seeks to ascertain the application of social media to reference services in academic libraries in Nigeria. Questionnaire instrument was used for data collection. Survey questionnaire was designed for library personnel involved in reference services in academic libraries in Nigeria. 100 copies of questionnaire were distributed to the librarians and other library personnel at the National seminar in 2011 held at Kogi State University, Nigeria. 62 copies were filled and returned, given a response rate of 62%. The study found that the rate of use of social media platforms for reference services by academic library personnel in Nigeria is very low as a result of lack of awareness and training on the various kinds of social media and their application to reference services, infrastructural and technological problems amongst others. The study advocated attitudinal change on the part of librarians, awareness and advocacy on the use of social media within the academic community, provision of appropriate infrastructure and workshops on the use of social media in reference services as solutions to the use of social media for reference services in academic libraries in Nigeria.